Standardization and Antioxidant Activity Test of Karamunting Leaf Extract (Melastoma malabathricum L.) Using the DPPH Method - Haryoto Haryoto; Ahmad Fauzi; Herda Ariyani; Danang Raharjo; Erlinda Novita Sari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Karamunting leaves (Melastoma malabathricum L.) are a typical plant of Kalimantan, empirically used by local communities as traditional medicine to treat diarrhea, dysentery, vaginal discharge, mouth ulcers, and to enhance immune function. The presence of phenolic compounds, flavonoids, and saponins in karamunting leaves indicates their potential as natural antioxidant agents. Standardization of simplicia and extracts is an essential prerequisite to ensure the quality, safety, and consistency of traditional medicinal raw materials in a scientific and measurable manner. Objective: This study aimed to standardize the 70% ethanol extract of karamunting leaves through specific and non-specific parameter testing and to evaluate its antioxidant activity using the DPPH method. Methods: Extraction was performed using the maceration method with 70% ethanol solvent for 24 hours. Standardization included specific parameter tests (organoleptic and phytochemical screening) and non-specific parameter tests (water content, drying loss, total ash content, acid-insoluble ash content, heavy metal contamination of Pb and Cd, as well as ethanol-soluble and water-soluble extractive values) in accordance with the Indonesian Herbal Pharmacopoeia (FHI) Edition II standards. Antioxidant activity was assessed using the DPPH radical scavenging method and expressed as the IC₅₀ value. Results: The karamunting leaf extract exhibited a thick consistency, green color, characteristic odor, and bitter taste. Phytochemical screening showed positive results for phenolic compounds (blue-black coloration with FeCl₃) and flavonoids (orange coloration with Mg/HCl). Non-specific parameter testing revealed water content of 15.05±0.36%, drying loss of 6.54±0.51%, total ash content of 3.40±0.31%, acid-insoluble ash content of 0.79±0.02%, and ethanol-soluble and water-soluble extractive values of 98.52% and 96.60%, respectively. No Pb and Cd heavy metal contamination was detected. The antioxidant activity assay yielded an IC₅₀ value of 54.63±1.97 ppm, which falls into the strong antioxidant category, although it remained lower than vitamin C (IC₅₀=8.80±1.27 ppm). Conclusion: The karamunting leaf extract has met the quality parameter requirements according to FHI standards and demonstrates significant potential as a source of natural antioxidants. Further research is required for the identification of specific active compounds, quantitative heavy metal analysis using AAS, and in vivo activity testing to confirm its efficacy and safety.